Management of a respiratory syncytial virus outbreak in a memory care unit at a long-term care facility - Alaina S. Ritter; Debbie Manderville; Laura Netardus; Amy Y. Vittor (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Abstract